A systematic review of prehabilitation programs in abdominal cancer surgery. (March 2017) - Hijazi, Yasser; Gondal, Umair; Aziz, Omer
Abstract: Introduction: Prehabilitation programs aim to optimise patients in order to enhance post-operative recovery. This study aims to review the composition of prehabilitation programs for patients undergoing major abdominal cancer surgery and define the outcome measures that are used to evaluate this intervention. Methods: A systematic literature review of all comparative studies on prehabilitation versus standard care in patients undergoing abdominal cancer surgery was performed in accordance with PRISMA guidelines. Literature search was performed using Medline, OVID, EMBASE, Google Scholar, and Cochrane databases. Outcomes of interest included prehabilitation program composition (exercise, nutritional, and psychological interventions), duration, mode of delivery, and outcome measures used to determine impact of prehabilitation versus standard care. Results: 9 studies (7 randomised controlled and 2 prospective non-randomised trials) comprising of 549 patients (281 prehabilitation versus 268 standard care) were included in this review. 5 studies reported patients undergoing surgery for colorectal cancer, 2 for bladder tumours, 1 for liver resections, and 1 involving unspecified abdominal oncological operations. The 6 min walk test (6MWT) was used in 4 studies to measure functional capacity with a threshold of >20 m improvement at 4–8 weeks post-operatively deemed significant (distance range from 278 to 560 m). Changes in anaerobic threshold and VO2 max with prehabilitation were evaluated in 5 studies (ml/kg/min). Health-related quality of life was evaluated using SF-36 system, anxiety assessed using hospital anxiety and depression score (HADS). Post-operative complications were classified according to the Clavien-Dindo classification with no significant difference between prehabilitation and standard care groups. Conclusion: Prehabilitation programs in patients undergoing abdominal cancer surgery remain heterogeneous in their composition, mode of administration, outcome measures of functional capacity that are used to evaluate their impact. All these aspects require standardisation prior to the evaluation of prehabilitation on a larger scale. Highlights: Prehabilitation programs are heterogeneous in terms of composition, modes of delivery and duration. Outcome measures used to quantify the impact of prehabilitation programs were also heterogeneous between studies. All these aspects require standardisation prior to the evaluation of prehabilitation on a larger scale.